2016
DOI: 10.3906/zoo-1412-2
|View full text |Cite
|
Sign up to set email alerts
|

Dung beetles (Coleoptera: Scarabaeidae) utilizing water buffalo dungon the Black Sea coast of Turkey

Abstract: There have been few ecological studies of dung beetles (Coleoptera: Scarabaeidae) from the Black Sea Region of Turkey. In the RAMSAR-listed wetland system of the Kızılırmak Delta of Turkey's central Black Sea coast, seasonal grazing by domesticated water buffalo produces plentiful dung from April to November. Twenty-three species of dung beetles from 13 genera of Aphodiinae and 4 genera of Scarabaeinae were collected from their dung on two adjacent soil types in 2013. The species were from three functional gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Such shift also occurs in time, for Aphodiinae dominate in abundance during the dry season throughout the whole gradient (totalling > 95% of individuals in all local communities), a pattern also found in other Mediterranean dung beetle assemblages (e.g. Sánchez-Piñero et al, 2004;Sullivan et al, 2016).…”
Section: Discussionsupporting
confidence: 54%
“…Such shift also occurs in time, for Aphodiinae dominate in abundance during the dry season throughout the whole gradient (totalling > 95% of individuals in all local communities), a pattern also found in other Mediterranean dung beetle assemblages (e.g. Sánchez-Piñero et al, 2004;Sullivan et al, 2016).…”
Section: Discussionsupporting
confidence: 54%
“…When VWC was limiting in the late season, increasing temperature was less conducive for plant root and microbial activities. Other studies also reported a strong soil VWC and soil temperature effect on the fluxes of CO 2 (Lloyd and Taylor, 1994; Smith et al, 2003; Balogh et al, 2011). …”
Section: Discussionmentioning
confidence: 78%
“…Dung beetles feed on the liquid contents of dung and use remaining dung material for housing and food for their brood. According to nesting strategies, dung beetles are grouped in three functional groups: (i) endocoprids (dweller), the beetles live and brood inside the dung pat; (ii) paracoprids (tunneler), the beetles dig burrows and construct nesting chambers with dung materials in the soil below the dung pats; and (iii) telecoprids (ball roller), the beetles form dung balls and roll them some distance away from the dung pat before burial into soil for their brood (Halffter and Edmond, 1982;Sullivan et al, 2016). The abundance of dung beetles increased colonization of dung by arthropods communities, which are major contributors to dung degradation (Pecenka and Lundgren, 2018).…”
mentioning
confidence: 99%
“…In Turkey, there is no study related to beetles with medical and veterinary importance. However, in a study, several species of dung beetles in Scarabaeidae family have been reported from the Black Sea region of Turkey (426).…”
Section: Cystoisosporiasis (Formerly Isosporiasis or Human Cocciddiosis)mentioning
confidence: 99%